Pembelajaran Berdiferensiasi pada Jenjang Pendidikan Sekolah Dasar - Firmansyah, Deni; Alfaidah, Hani; Dewi, Kurnia; Mustaniroh, Laila; Syifa, Nabila Aulia (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Learning at elementary school level should be carried out interactively, fun, effectively, and able to motivate students to participate actively, independently, and provide sufficient space for the development of talents, interests and creativity in learning activities. This goes straight with the basic concept of differentiated learning, namely that differentiated learning activities are an attempt to adjust the position of the learning process in the classroom to facilitate the different learning needs of each individual student. Therefore, researchers are interested in conducting a literature review regarding the implementation of differentiated learning at the elementary school level. Based on the results of the views and analysis of the literature review, it can be concluded that (1) the differentiated approach can be combined with several learning models that support differentiated learning (2) the implementation of differentiated learning is able to increase and improve student learning outcomes; (3) the differentiated approach can and is well used at the elementary school level because it is able to accommodate all students' learning needs by taking into account students' interests, talents, profiles, abilities, learning styles.